Pengaruh Kualitas Layanan Logistik terhadap Kepuasan dan Loyalitas Pelanggan Sociolla (The Influence of Logistics Service Quality on Sociolla Customer Satisfaction and Loyalty) - Lisa Lionnard; Fitri Novika Widjaja; Stefanus Budy Widjaja Subali (STIE Malangkucecwara, 2026)
This study aims to determine the effect of logistics service quality, ranging from order accuracy, order condition, timeliness, order discrepancy handling, and information quality on customer satisfaction, as well as the effect of customer satisfaction on customer loyalty in Sociolla e-commerce in Indonesia. This study uses a quantitative approach, with analysis using Structural Equation Modeling (SEM) through AMOS Graphics 23 software. Data collection was carried out by distributing questionnaires online through Google Forms with a total of 211 respondents. The results show that order accuracy, order condition, timeliness, order discrepancy handling, and information quality have a positive effect on customer satisfaction, and customer satisfaction has a positive effect on customer loyalty. These results emphasize the importance of logistics service quality in shaping a positive customer experience and strengthening the company's competitiveness in a competitive business environment.